Canadian food banks and the depoliticization of food insecurity at the individual and community levels - Carlson, Eleanor Anne (Canadian Review of Social Policy / Revue canadienne de politique sociale, 2014)
Canadian social scientists have frequently pointed out the necessity of understanding food banks and food insecurity as political in relation to the institutionalization of food banks and their collective interactions with federal, provincial, and corporate bodies. However, a comprehensive understanding of this role must additionally engage with discursive practices at the community level. Food banks, from which hundreds of thousands of Canadians each month receive temporary relief from hunger, offer a wealth of information in this regard. This research was conducted by means of a discourse analysis of documentation produced and collected by a prominent British Columbia food bank. Overall, 1,391 documents were analyzed, totaling 3,285 pages and covering the time period from 1989 to 2008. In this paper, I discuss three prominent discourses exposed through the analysis of these documents, one concerning individualization and immediacy in regard to those who are food insecure, another concerning community membership and responsibility, and a third concerning the differentiation of services provided to different food bank users. I conclude that the reproduction of these particular discourses, along with the implementation of particular policies and procedures within the food bank, are key processes through which the possibility of a political conceptualization of food insecurity is diminished at the individual and the community levels.